PENGARUH KOMUNIKASI GURU PPKn TERHADAP HASIL BELAJAR SISWA MTs DARUL- HIKMAH PEKANBARU - Mery Yanti; Sri Erlinda; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is motivated by the influence of PPKn TeacherCommunication Against Student Learning Outcomes. The formulation of the researchproblem is: "How do PPKn teacher communication at MTs Darul-Hikmah Pekanbaruschool?" "How do you learn about PPKn at the MTs Darul-Hikmah Pekanbaruschool?" Is there any effect of PPKn teacher communication on learning outcomes atthe MTs Darul-Hikmah Pekanbaru School? ". The purpose of the study was todetermine the communication of PPKn teachers at MTs Darul-Hikmah pekanbaru, tofind out the student learning outcomes in PPKn subjects at the MTs Darul-HikmahPekanbaru school and to find out the influence of PPKn teacher communication onstudent learning outcomes in PPKn subjects at Darul-Hikmah MTs Pekanbaru. Thisresearch was conducted at MTs Darul-Hikmah Pekanbaru in July 2018, this researchwas a quantitative descriptive population of 73 students with the straifet rendomsampling technique. Data collection instruments are questionnaires with a total of 16questions. Thus there is a positive influence of PPKn teacher communication on studentlearning outcomes ". This is evidenced by testing the hypothesis between Variable X andVariable Y, obtained by calculating F by 2,381, the Fcount value is then compared withthe Ftable value with a 95% confidence level, is 1,771 because Fcount> Ftable (2,381>1,771), then the hypothesis is accepted thus it was concluded that there was asignificant influence of teacher communication on learning outcomes with a coefficientof determination of 38.53 while 61.47% was influenced by other variables not includedin this study.Keywords: Teacher Communication, Learning Outcomes.